2018
DOI: 10.12659/msm.911124
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Dehydrogenase 1 (MTHFD1) is Underexpressed in Clear Cell Renal Cell Carcinoma Tissue and Transfection and Overexpression in Caki-1 Cells Inhibits Cell Proliferation and Increases Apoptosis

Abstract: BackgroundThe aims of this study were to investigate the expression of methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) in human tissue containing clear cell renal cell carcinoma (CCRCC) compared with normal renal tissue, and the effects of upregulating the expression of MTHFD1 in the human CCRCC cell line, Caki-1.Material/MethodsTumor and adjacent normal renal tissue were obtained from 44 patients who underwent radical nephrectomy for CCRCC. Caki-1 human CCRCC cells were divided into the control group, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, a study of 201 children with acute lymphocytic leukemia (ALL) treated with methotrexate showed that patients with high MTHFD1 expression had a lower OS rate 113 . However, MTHFD1 is underexpressed in clear cell renal cell carcinoma (ccRCC) tissue when compared with normal renal tissues, which inhibits cancer cell proliferation and induces cell apoptosis 114 . In summary, MTHFD1 is controversial as a diagnostic marker but may be a new tumor‐specific therapeutic target for anti‐folate drugs in cancers with high MTHFD1 expression.…”
Section: Serine‐glycine‐one‐carbon Metabolic Enzymes In Tumorsmentioning
confidence: 99%
“…In addition, a study of 201 children with acute lymphocytic leukemia (ALL) treated with methotrexate showed that patients with high MTHFD1 expression had a lower OS rate 113 . However, MTHFD1 is underexpressed in clear cell renal cell carcinoma (ccRCC) tissue when compared with normal renal tissues, which inhibits cancer cell proliferation and induces cell apoptosis 114 . In summary, MTHFD1 is controversial as a diagnostic marker but may be a new tumor‐specific therapeutic target for anti‐folate drugs in cancers with high MTHFD1 expression.…”
Section: Serine‐glycine‐one‐carbon Metabolic Enzymes In Tumorsmentioning
confidence: 99%